El marco institucional de la agricultura familiar en Costa Rica - Rivera Romero, Federico (2012)
The purpose of this study of the universe is to answer the following questions: Who are they, and where are located many family farmers who will suffer and benefit from trade liberalization and public policy in the sector?, What are the potential expected impacts of trade liberalization on the agricultural sector? and what are the most efficient tools and programs with which governments have to support this sector? These are some of the fundamental questions of the current government agenda, questions on which this study aims to deepen and help structure responses.